2015
DOI: 10.1364/boe.6.004585
|View full text |Cite
|
Sign up to set email alerts
|

Modular platform for low-light microscopy

Abstract: Cell imaging using low-light techniques such as bioluminescence, radioluminescence, and low-excitation fluorescence has received increased attention, particularly due to broad commercialization of highly sensitive detectors. However, the dim signals are still regarded as difficult to image using conventional microscopes, where the only low-light microscope in the market is primarily optimized for bioluminescence imaging. Here, we developed a novel modular microscope that is costeffective and suitable for imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The pattern of binding of [ 18 F]HFB, consisting of preferential binding to fragmented membranes of non-viable cells, has not been observed with other PET radiolabels. Previously, radioluminescence microscopy has been applied to imaging of 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)-butyl]guanine ([ 18 F]FHBG) uptake in HeLa cells expressing herpes simplex type 1 virus (HSV1) thymidine kinase [29], binding of [ 64 Cu]rituximab in single Ramos B lymphocytes [39], uptake of [ 18 F]FDG [30,40] and 3′-deoxy-3′-[ 18 F-]fluorothymidine ([ 18 F]FLT) [41] in MDA-MB-231 cells. In these studies, binding of the radiolabel was only observed in viable cells, with minimal background, ruling out the possibility of a technical artefact.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of binding of [ 18 F]HFB, consisting of preferential binding to fragmented membranes of non-viable cells, has not been observed with other PET radiolabels. Previously, radioluminescence microscopy has been applied to imaging of 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)-butyl]guanine ([ 18 F]FHBG) uptake in HeLa cells expressing herpes simplex type 1 virus (HSV1) thymidine kinase [29], binding of [ 64 Cu]rituximab in single Ramos B lymphocytes [39], uptake of [ 18 F]FDG [30,40] and 3′-deoxy-3′-[ 18 F-]fluorothymidine ([ 18 F]FLT) [41] in MDA-MB-231 cells. In these studies, binding of the radiolabel was only observed in viable cells, with minimal background, ruling out the possibility of a technical artefact.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we developed a “low-light microscope” (LLM) to offer a cost-effective and modular alternative to commercial bioluminescence microscopes 18 . This system is entirely constructed from commercial lenses and optomechanical parts.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the microscope enables a level of performance comparable to commercial bioluminescence microscopes (e.g. LV200), except for a minor reduction in field-of-view (∼30% area) due to the smaller physical aperture of the 4× objective used as tube lens 18 . Since the microscope is highly modular, the setup can be tailored to the researcher's needs, and additional capabilities such as microfluidics, intravital imaging or motorized X-Y stage can be added 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the challenging nature of imaging radionuclides at the single‐cell level with high sensitivity, the performance of RLM in terms of spatial resolution and sensitivity must be as high as possible. Currently, the design of the microscope (eg, the parameters of the microscopy objective, scintillator and camera) has been optimized empirically, through trial and error . For instance, a 10‐μm thin Lu 2 O 3 scintillator has been used in some experiments to enhance spatial resolution and sensitivity.…”
Section: Introductionmentioning
confidence: 99%